Dental Caries and Treatment Needs among Kindergarten Children in Al-Basrah Governorate/Iraq - Al-Abbasi, Sarah W.; Radhi, Nada J.M.H. (Journal of Baghdad College of Dentistry, 2016)
Background: Dental caries is a disease occurs in the world in both developed and developing countries, it is still widespread among children and it can be controlled but not eliminated , most of tooth loss occurs due to dental caries and its complications. The aim of this study was to estimate the occurrence, and severity of dental caries and treatment needs among kindergarten children in Al-Basrah governorate. Materials and methods: The sample consisted of 1000 kindergarten children at age of 4-5 years old (445 boys and 555 girls) from urban areas in Al-Basrah city. Diagnosis and recording of dental caries and treatment needs were done according to the criteria of WHO (1987). Results: The percentage of dental caries was (80.8%) of the total sample. The dmfs value was higher among boys compared to girls with no statistically significant difference (P>0.05).The dmfs value among 5 years old children were found to be higher than children aged 4 years with statistically highly significant difference (P< 0.01). The higher percentage of examined children was in need of one surface filling (71.6%) followed by those in need of preventive or fissure sealant (61.3%). Conclusions: A study revealed a high prevalence of dental caries was found among Kindergarten children in Al-Basrah governorate, thus there is a need for preventive programs among those children.